Sickened: The True Story of A Lost Childhood - Julie Gregory
From early childhood, Julie Gregory was continually X-rayed, medicated, and operated on in the vain pursuit of an illness that was created in her mother's Munchausen by Proxy, the world's most hidden and dangerous form of child abuse. Sickened is her story. Readers of Educated, The Glass Castle and The Memory Palace will want to read this.